CHARACTERISTICS OF ADRENAL GLAND PATHOMORPHOLOGY IN MATERNAL DEATH - Shokirov, Khumoyunmirzo; Mamataliyeva, Mavlyuda (Medical science of Uzbekistan, 2025)
The relevance of the problem. Maternal mortality is a pressing problem in the world, and although what is being done has a certain result, it is observed at a high level. The purpose of the study was to investigate specific aspects of the pathomorphology of the adrenal gland in maternal mortality, observed during pregnancy and in the first week of the postpartum period. Research method and material. The study investigated the specific aspects of the pathomorphology of the adrenal gland in the archival materials of autopsy in maternal deaths, observed during 75 pregnancies and in the first week of the postpartum period in Uzbekistan during 2015-2024. Study result. The accumulation of lipid infusions instead of basophilic inclusions in adrenocorticocytes in the buttockular area of the coarse layer showed important diagnostic value in morphological investigation of processes associated with preeclampsia. Conclusion. One of the pathomorphological features of the adrenal gland in maternal mortality is a violation of connectivity in the sympathoadrenal system, which continues with dysfunction of the adrenal gland, central circulatory disorders, leading to a violation of haemodynamic parameters in all organs, perfusion in peripheral blood vessels, polyorgan failure. The main nonspecific response reaction, which is characteristic of the adrenal gland in maternal mortality of different aetiologies, is associated with diapedesis blood transfusion in the buttocks area of the adrenal layer, multifocal necrosis in spongiostitis, an increase in lipid infiltration and necrobiosis in the stitoplasm of cells, massive haemorrhagic foci in the urinary cavity and the formation of foci with sharply changed histioarchitectonics after necrosis, and acute renal gland failure. It was characterised by the presence of morphological changes. These changes mainly serve as a direct stepping stone to the mechanism of tanogenesis of the occurrence of maternal mortality in pregnancy.